(x-2)²-25 =0 by factorsation method
Answers
Answered by
9
answer in the pic....
hope this helps and please mark my answer as brainliest.....
hope this helps and please mark my answer as brainliest.....
Attachments:
![](https://hi-static.z-dn.net/files/d64/9c26a936e2f00497c61f30fadac2fbc2.jpg)
neha600:
thank you so much brother
Answered by
6
Do it by the formula
![{a}^{2} - {b}^{2} =( a + b)(a - b) {a}^{2} - {b}^{2} =( a + b)(a - b)](https://tex.z-dn.net/?f=+%7Ba%7D%5E%7B2%7D+++-++%7Bb%7D%5E%7B2%7D++%3D%28+a+%2B+b%29%28a+-+b%29)
So here...
![{(x - 2)}^{2} - {5}^{2} = 0 {(x - 2)}^{2} - {5}^{2} = 0](https://tex.z-dn.net/?f=+%7B%28x+-+2%29%7D%5E%7B2%7D++-++%7B5%7D%5E%7B2%7D++%3D+0)
Which implies.... (x-2+5)(x-2-5)
(x+3)(x-7)... This is ur answer
Hope it helps!
So here...
Which implies.... (x-2+5)(x-2-5)
(x+3)(x-7)... This is ur answer
Hope it helps!
Similar questions